Death penalty - human (?) aspect - Bespala, T. (ХНУ ім. В. Н. Каразіна, 2012)
This article deals with the death penalty. The definition of the death penalty seems somehow inadequate when it is compared to the crime. It is a paragon of situational ethics, and solid moral arguments are slim. But, the facts against the death penalty are less vague. Concrete examples of false convictions, unnecessary pain, and barbaric practices can be found in this article. Due to the imperfect nature of human behavior, no human entity possesses the arbitrary ability to end the life of another human being.
В этой статье рассматривается смертная казнь. Определение смертной казни кажется так или иначе неадекватным, иногда даже её сравнивают с преступлением. Это - образец ситуативной этики, и твердые моральные аргументы тонки. Но, факты против смертной казни неопределенны. В данной статье рассматриваются конкретные примеры ложных осуждений, ненужной боли, и варварских методов. Из-за несовершенной природы человеческого поведения, никто из людей не обладает произвольной властью закончить жизнь другого человека.
Keywords: death penalty; penalty; human behavior; justice ability; crime